2018
DOI: 10.3390/molecules23112794
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Integrated Way for Deciphering the Glycan Code for the FimH Lectin

Abstract: The fimbrial lectin FimH from uro- and enteropathogenic Escherichia coli binds with nanomolar affinity to oligomannose glycans exposing Manα1,3Man dimannosides at their non-reducing end, but only with micromolar affinities to Manα1,2Man dimannosides. These two dimannoses play a significantly distinct role in infection by E. coli. Manα1,2Man has been described early on as shielding the (Manα1,3Man) glycan that is more relevant to strong bacterial adhesion and invasion. We quantified the binding of the two diman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
1
13
0
1
Order By: Relevance
“…The catch-bond mechanism of FimH was established by characterizing the binding of the model ligand n -heptyl α- d -mannopyranoside (HM) to a soluble, monomeric version of full-length FimH, FimH·DsG, in which FimH P was stabilized with a synthetic peptide corresponding to DsG, and the isolated FimH L domain representing the S-state of FimH under shear force (Figure a) . Within the urinary tract environment, FimH recognizes a variety of glycoproteins, including uroplakin 1a, β1 and α3 integrins, and uromodulin. ,, All these glycoproteins present high-mannose type N -glycans on their surface with glycoforms ranging from Man 5 Gn 2 to Man 9 Gn 2 and terminally exposed α- d -mannopyranosides that can be either α(1–2)-, α(1–3)-, or α(1–6)-linked to the respective N -glycan (Figure b). Notably, previous studies indicated that FimH L more readily binds to α(1–3)-linked versus α(1–2)-linked and α(1–6)-linked dimannosides. , However, fundamental questions on the interactions between FimH and its natural N -glycan binding epitopes remained unresolved: (i) How does FimH bind the different terminal mannosides at the structural level? (ii) How do the different conformational states of FimH affect binding kinetics to their natural binding epitopes?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The catch-bond mechanism of FimH was established by characterizing the binding of the model ligand n -heptyl α- d -mannopyranoside (HM) to a soluble, monomeric version of full-length FimH, FimH·DsG, in which FimH P was stabilized with a synthetic peptide corresponding to DsG, and the isolated FimH L domain representing the S-state of FimH under shear force (Figure a) . Within the urinary tract environment, FimH recognizes a variety of glycoproteins, including uroplakin 1a, β1 and α3 integrins, and uromodulin. ,, All these glycoproteins present high-mannose type N -glycans on their surface with glycoforms ranging from Man 5 Gn 2 to Man 9 Gn 2 and terminally exposed α- d -mannopyranosides that can be either α(1–2)-, α(1–3)-, or α(1–6)-linked to the respective N -glycan (Figure b). Notably, previous studies indicated that FimH L more readily binds to α(1–3)-linked versus α(1–2)-linked and α(1–6)-linked dimannosides. , However, fundamental questions on the interactions between FimH and its natural N -glycan binding epitopes remained unresolved: (i) How does FimH bind the different terminal mannosides at the structural level? (ii) How do the different conformational states of FimH affect binding kinetics to their natural binding epitopes?…”
Section: Introductionmentioning
confidence: 99%
“…29−34 Notably, previous studies indicated that FimH L more readily binds to α(1−3)-linked versus α(1−2)-linked and α(1−6)-linked dimannosides. 35,36 However, fundamental questions on the interactions between FimH and its natural N-glycan binding epitopes remained unresolved: (i) How does FimH bind the different terminal mannosides at the structural level? (ii) How do the different conformational states of FimH affect binding kinetics to their natural binding epitopes?…”
Section: ■ Introductionmentioning
confidence: 99%
“…The free binding energies were calculated for all the native-protein (4XO9 and 4X5P) and ligand–protein (b to k) complexes using the MM-PBSA/MM-GBSA methods. Dumych et al [ 45 ] reported that the Poisson–Boltzmann free binding energy (MM-PBSA) method shows the same trend as in vivo tests. In both cases, the native-protein complexes have a negative free energy, which is consistent with the fact that experimentally, it is possible to observe these complexes.…”
Section: Resultsmentioning
confidence: 96%
“…FimH has two protein domains: the pilus‐linking pilin domain and the distal lectin domain, which binds carbohydrates [ 38 , 40 ]. The FimH lectin domain binds terminal mannose(α1,3)‐mannose residues with high affinity and, to a lesser extent, mannose(α1,2)‐mannose and mannose (α1,6)‐mannose [ 41 , 42 ]. These constitute the terminal moieties of high‐mannose N‐glycans, which are particularly abundant on UP1a and integrin α3β1 [ 36 , 43 , 44 ].…”
Section: Carbohydrates Directly Mediate Upec Attachment Internalization and Proliferationmentioning
confidence: 99%